Pelaksanaan Perjanjian Kredit Dengan Jaminan Hak Tanggungan Pada PT. BPR Danayasa - Desak Made Widyaswari; H. Zaenal Arifin Dilaga; Allan Mustafa Umami (Private Law, 2023)
This study aims to determine the procedures for implementing a credit agreement guaranteed by Mortgage, and the obstacles in implementing a credit agreement guaranteed by Mortgage at BPR Danayasa Ltd. The method used in this study is Normative-Empirical, which is carried out by researching and processing existing facts with field observations and then studying them to solve problems. Based on this research, it is concluded that the procedure for implementing credit with Mortgage guarantees starts from filling out the credit application file by the prospective customer to the final process, namely the granting of a Mortgage, obstacles in implementing credit agreements with Mortgage guarantees including juridical and non-juridical obstacles, settlement of non-performing loans, namely approach to the debtor and sell debtor collateral.